A prospective comparative study of potential risk factors between Ludwig's angina and localised odontogenic abscesses - Chettiar, Thoganthiren Perumal (My University, 2008)
ABSTRACT Odontogenic abscesses and Ludwig’s angina are infections commonly seen by maxillofacial surgeons. Both infections have periapical or periodontal origin and caused by oral bacteria. Ludwig’s angina is an aggressive and fast spreading infection compared to odontogenic abscess. The origin and the responsible bacteria of these infections are similar but the development and response is different in patients. There is no comprehensive study that has investigated the bacterial and host factors involved in the development of there infections. The aim of this study was to compare the presence of bacteria and enzymes in to the pus samples collected from patients with odontogenic abscess and Ludwig’s angina. Furthermore, various haematological and immunological tests were also compared between the two study groups. Forty two patients presenting with localized odontogenic abscesses and 15 with Ludwig’s angina were selected. Patient was examined according to standard protocol and history was recorded. Bloods were collected for haematology and immunology tests and pus was collected for microbiology and enzymatic tests. The results showed that highly virulent bacteria such as Staphylococcus aureus and black pigmented bacteroides were prevalent, increase in c-reactive protein, white blood cell count, IL6 and decrease in urea, circulating immune complexes and IgE in patients with Ludwig’s angina. Development of Ludwig’s angina could be due to the aggressive bacteria, their byproducts and low immune response compared to the odontogenic abscesses.
Keywords: Ludwig's angina; localised odotogenic abscesses; risk factors